Implementasi Metode Waterfall Pada Rancang Bangun Sistem Informasi Manajemen Aset Di SMK Muhammadiyah 3 Karanganyar - Aziz, Al Fath Abdul; Maryam, Maryam (STMIK Sinar Nusantara, 2024)
Asset management is an important aspect in an organization in the form of a series of activities related to identifying required assets, identifying funding needs, acquiring assets, providing logistical support, asset maintenance systems, and deleting or renewing assets. Problems that occur with conventional management include inefficient management processes, limited access to information, and difficulties in tracking borrowed assets and repairing and maintaining assets. Information systems are technology-based solutions that can be used to support asset processing performance to make it more effective and efficient. This research explains the steps in developing an asset management system at SMK Muhammadiyah 3 Karanganyar. System development involves the waterfall method, including requirements analysis, system design, implementation, testing, and maintenance. Its features include asset recording, tracking asset loan and return transactions, maintenance tracking, as well as providing reports and analyses that support informed decision making by organizations. The implementation of this system is expected to improve transparent and accurate asset management, reduce losses due to unrecorded inventory and minimize human error in recording transactions. The system was built using PHP programming language with Code Igniter framework and MySQL as the database. Based on the results of system testing using the black box method, it shows that the system works according to its function. Meanwhile, the test results using SUS method obtained an assessment of 80.3 which was stated in Acceptable Range with a Scale Value of A, which means good. Thus, the system is suitable for use by users. This shows that the system has the potential to increase efficiency and better asset management.